Farmer’s perception on fertilizer management using Ajinomoto byproduct for high market value local rice varieties in irrigated lowlands in Côte d’Ivoire - Arouna, Aminou; Gbede, T. R. (Africa Rice Center, 2024)
This work presents results of the socioeconomic evaluation of the Ajinomoto fertilizer (AF) experimentation demonstrations among rice farmers in Côte d’Ivoire. The focus was on assessing the perception of rice farmers on the AF experimentation and demonstrations from both the intervention participants and non-participants. Three regions in Côte d’Ivoire were covered as part of the survey and data were collected from a randomly sampled 270 rice farmers through face-to face individual interviews using CSPro application installed on android tablets. Data collected we submitted to both descriptive and inferential statistics for analysis by means of the Stata version 18 and SPSS software. Results showed that majority of famers grew rice in wet season (72%), used on average 6 days for cleaning and preparation of seeds before planting, used transplanting as the major sowing method (91%), applied both NPK and Urea fertilizer only when soil is wet (67%), but did not pay attention to soil condition to apply pesticide. Farmers mainly expected fertilizer to be able to, among other things, increase the rice yield, allow good filling of the grains and increase the number of grains per panicle. The popular fertilizers currently used by farmers included the NPK (12-22-22), the combined NPK (15-15-15) & Urea (N, 46%), and the combined NPK (12-22-22) & Urea (N, 46%). In both groups of farmers, similar pieces of land were allocated to rice production with a mean value of 2.7 ha. The average yield was 3.1 tons/ha, with a significantly higher yield in the participation group than in the non-participation group. Regarding the Ajinomoto fertilizer technology, findings unsurprisingly showed highly significant differences in terms of knowledge and use of Ajinomoto fertilizer between participant and non participant farmers. Overall, participants had a very good awareness and experience with the AF and were willing to adopt it. More than half of farmers (61%) were aware of the AF, including nearly half of non-participant farmers (42%) in addition to 100% of participant farmers. Up to 94% of non-participants in addition to 100% of participants were willing to use the AF and ready to apply it on 82.68% of their total area cultivated to rice, resulting in a total area of 2.33 ha of land to be under the AF use. Furthermore, rice farmers (75%) were also willing to extend the application of the AF to other crops apart from rice. In terms of their perception on the performance of the technology compared to other fertilizers used, participant farmers agreed with all the sixteen (16) statements on the performance of the AF, in comparison to the other fertilizers they used.